2021
DOI: 10.3389/fphys.2021.707389
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Kinase Is Required for Sex Pheromone Biosynthesis in Helicoverpa armigera

Abstract: Pyruvate kinase (PYK) is a speed-limited enzyme of glycolysis that catalyzes the formation of pyruvate, and plays an important role in acetyl-CoA synthesis. The acetyl-CoA is the precursor of sex pheromone biosynthesis in Helicoverpa armigera. However, the role of PYK in sex pheromone biosynthesis remains elusive. Here, PYK in H. armigera (HaPYK) was found to be highly expressed in the pheromone glands (PGs). The developmental expression profile of HaPYK was consistent with the fluctuation of sex pheromone rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Thus, sugar feeding markedly increases the concentrations of trehalose and acyl‐CoA in PG, and ultimately facilitating sex pheromone biosynthesis is easy to understand. These views were also confirmed in H. armigera , in which, the knockdown of HaPYK , a rate‐limiting enzyme in glycolysis, reduces acetyl‐CoA contents, and consequently, decreases sex pheromone production (Yao et al, 2021). Acetyl‐CoA is known to be produced via glycolysis and tricarboxylic acid cycle by using glucose as a material (Foster & Anderson, 2015).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Thus, sugar feeding markedly increases the concentrations of trehalose and acyl‐CoA in PG, and ultimately facilitating sex pheromone biosynthesis is easy to understand. These views were also confirmed in H. armigera , in which, the knockdown of HaPYK , a rate‐limiting enzyme in glycolysis, reduces acetyl‐CoA contents, and consequently, decreases sex pheromone production (Yao et al, 2021). Acetyl‐CoA is known to be produced via glycolysis and tricarboxylic acid cycle by using glucose as a material (Foster & Anderson, 2015).…”
Section: Discussionmentioning
confidence: 79%
“…These findings clearly indicate the importance of sugar supplements in female adults. Furthermore, data from H. virescens , M. separata , and H. armigera demonstrated that sugar feeding increases trehalose content and sex pheromone production, demonstrating the importance of supplemental nutrition in sex pheromone biosynthesis (Foster, 2009; Foster & Anderson, 2015; Yao et al, 2021; Y. Zhang et al, 2020). Acetyl‐CoA acts as the precursor in sex pheromone biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations